2012
DOI: 10.2190/ec.47.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation in Secondary School Students' Structured and Unstructured Chat Discussions

Abstract: Joint construction of new knowledge demands that persons can express their statements in a convincing way and explore other people's arguments constructively. For this reason, more knowledge on different means to support collaborative argumentation is needed. This study clarifies whether structured interaction supports students' critical and elaborative argumentation.The study compares the quality of secondary school students' argumentation during structured and unstructured chat interaction. The data consist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…Prompts during the task were not given. In argumentative tasks, a topic has been found to have an important role in students’ engagement in active, argumentative discussions (Salminen, Marttunen, & Laurinen, in press; Udell, 2007; Zohar & Nemet, 2002). The topic of Internet censorship was chosen for several reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Prompts during the task were not given. In argumentative tasks, a topic has been found to have an important role in students’ engagement in active, argumentative discussions (Salminen, Marttunen, & Laurinen, in press; Udell, 2007; Zohar & Nemet, 2002). The topic of Internet censorship was chosen for several reasons.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, while in the previous studies male students have been found to be dominating and to have a more assertive, competitive, and adversarial conversation style compared to females (Prinsen et al 2007;Carr, Cox, Eden, and Hanslo 2004), female students have been found to be more attuned to the task and willing to collaborate (Prinsen et al 2007). Thus, from the point of view of learning through constructive argumentation, gender differences in communication styles should not be seen as an obstacle but, rather, as a benefit for both male and female students (Robertson, Hewitt, and Scardamalia 2003;Salminen, Marttunen, and Laurinen 2012). Males, through their assertive and adversative communication style can provide a challenging space for knowledge construction, while females, for their part, can maintain argumentative discussion and facilitate argument elaboration through collaborative efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of discussion topic and situation for students' argumentation has been noticed in many studies. Topics which include authentic problems or provide relevant connections to students' lives may foster their argumentation performance (Salminen, Marttunen, and Laurinen 2012;Udell 2007;Zeidler, Sadler, Applebaum, and Callahan 2009;Zohar and Nemet 2002). Previous studies have also shown that even young children understand and are able to generate the main components of an argument in social situations personally significant to them (see Stein and Albro 2001).…”
Section: Role Play In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Algunos trabajos sobre buenas prácticas en el diálogo se han centrado en analizar las habili dades sociocognitivas, de carácter instrumen tal, para razonar y argumentar un punto de vis ta (GarcíaMila, Gilabert, Erduran y Felton, 2013;Salminen, Marttunen y Laurinen, 2012). Otros han subrayado el papel de las habilidades dialógicas de colaboración, entre las cuales ocu pa un lugar destacado la escucha activa, que requiere manejar adecuadamente las preguntas, dar o pedir explicaciones adicionales para clari ficar las posiciones y pedir confirmación para asegurarse de que se ha entendido (Meadows, 2013).…”
Section: Los Retos Que Plantea La Investigación Educativaunclassified